2018
DOI: 10.1371/journal.pone.0201073
|View full text |Cite
|
Sign up to set email alerts
|

Human gut bacteria as potent class I histone deacetylase inhibitors in vitro through production of butyric acid and valeric acid

Abstract: Overexpression of histone deacetylase (HDAC) isoforms has been implicated in a variety of disease pathologies, from cancer and colitis to cardiovascular disease and neurodegeneration, thus HDAC inhibitors have a long history as therapeutic targets. The gut microbiota can influence HDAC activity via microbial-derived metabolites. While HDAC inhibition (HDI) by gut commensals has long been attributed to the short chain fatty acid (SCFA) butyrate, the potent metabolic reservoir provided by the gut microbiota and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 47 publications
2
132
1
2
Order By: Relevance
“…Pathways of interest involve SCFA-induced HDAC inhibition. SCFAs have been reported as potent HDACis with important effects on histone modifications 36,49,50 including a recent study demonstrating that gut microbiota can influence HDAC activity via microbial-derived metabolites such as butyrate and valerate 49 . A recent study has also shown that the intestinal microbiota can mediate daily metabolic cycles epigenetically via the rhythmic induction of HDACs in epithelial cells of the small intestine 22 whereas previous studies have suggested the importance of HDACs in regulating circadian rhythms of hepatic lipid metabolism 20 and their roles in diet induced obesity and rhythmicity of the lipidome 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathways of interest involve SCFA-induced HDAC inhibition. SCFAs have been reported as potent HDACis with important effects on histone modifications 36,49,50 including a recent study demonstrating that gut microbiota can influence HDAC activity via microbial-derived metabolites such as butyrate and valerate 49 . A recent study has also shown that the intestinal microbiota can mediate daily metabolic cycles epigenetically via the rhythmic induction of HDACs in epithelial cells of the small intestine 22 whereas previous studies have suggested the importance of HDACs in regulating circadian rhythms of hepatic lipid metabolism 20 and their roles in diet induced obesity and rhythmicity of the lipidome 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, M. massiliensis produced significant levels of valeric acid and hexanoic acid, which are medium-chain fatty acids. It was also reported that valeric acid and butyrate cumulatively showed inhibition against Class I HDACs-HDACs1, 2, 3 8, particularly HDAC2 (Yuille et al, 2018).…”
Section: Histone Modifications and Chromatin Remodelingmentioning
confidence: 93%
“…Histone deacetylases (HDACs) constitute a class of enzymes that remove an acetyl group from the amino-terminal lysine residues of histones resulting in compacted chromatin (Yuille et al, 2018). Histone deacetylation is primarily associated with transcriptional inactivation and overexpression of HDACs and has been linked to a number of neurological and inflammatory diseases.…”
Section: Histone Modifications and Chromatin Remodelingmentioning
confidence: 99%
See 2 more Smart Citations